(3fXQjI GdeMGSHI GdeGdjI (B:s (3GdfehPL GdOhdj GdLOjO (B/s - (3LeYI, GMeO Mdejs ((3YeGf(B: s (3OGQ UaGA(B, s, 2010)
(3WHjYI GdGWGQ GdeaGgjej dGYOGO GdHjGfGJ GdeGdjI , WHjYI gjcd YQV GdHjGfGJ GdeGdjI, WHjYI GdeMGSHI Yf GdGjQGO h GdeNUUGJ h GdeNRhf , WHjYI GdeMGSHI Yf GdGUhd GdedehSI h ZjQ GdedehSI(B.s
(3eQGLY U(B.377 (3edGMb U(B351 (3,(B360s
Keywords: (3GdeGdjIs; (3GdeMGSHIs; (3GdeMGSHI GdeGdjIs